American Society of Nephrology Quiz and Questionnaire 2013: Electrolyte and Acid-Base - Palmer, Biff F. (American Society of Nephrology, 2014)
The Nephrology Quiz and Questionnaire (NQ&Q) remains an extremely popular session for attendees of the annual meeting of the American Society of Nephrology. As in past years, the conference hall was overflowing with interested audience members. Topics covered by expert discussants included electrolyte and acid-base disorders, glomerular disease, ESRD/dialysis, and transplantation. Complex cases representing each of these categories along with single-best-answer questions were prepared by a panel of experts. Prior to the meeting, program directors of United States nephrology training programs answered questions through an Internet-based questionnaire. A new addition to the NQ&Q was participation in the questionnaire by nephrology fellows. To review the process, members of the audience test their knowledge and judgment on a series of case-oriented questions prepared and discussed by experts. Their answers are compared in real time using audience response devices with the answers of nephrology fellows and training program directors. The correct and incorrect answers are then briefly discussed after the audience responses, and the results of the questionnaire are displayed. This article recapitulates the session and reproduces its educational value for the readers of CJASN. Enjoy the clinical cases and expert discussions.